Continuing Investigations of the Relationship Between Fin Whales, Zooplankton Concentrations and Hydrothermal Venting on the Juan De Fuca Ridge - Wilcock, William S; Thomson, Richard E (2013)
We are investigating the potential correlation between fin whale tracks, enhanced zooplankton concentrations and hydrothermal vents above the Juan de Fuca Ridge. Our goal is to understand the influences of globally distributed hydrothermal plumes on the trophic ecology of the deep ocean.